Criminal investigation on the street - Hildebrand, G. W. (Routledge, 2022)
"Criminal Investigation on the Street presents investigative principles and techniques-and applies them to solving real-world crimes-in an engaging, student-friendly style centered on the Investigative Triangle: legal aspects, evidence, and behavioral analysis. Students and instructors alike will benefit from this book's comprehensive coverage and accessible writing style. Along with the Investigative Triangle model, which provides a solid framework for approaching investigations, students will also learn about Criminal Investigative Analysis, a range of behavior-based services and strategies to help solve crimes. Chapters 1-7 (Section I) present the principles and techniques of criminal investigation-history and theory, legal background, forensics, crime scene, witnesses and informants, interviews and interrogations-including a chapter on crime analysis and Criminal Investigative Analysis. Chapters 8-13 (Section II) apply these principles and techniques to specific types of crime, beginning with assault and death investigations and a separate chapter on culpable homicide. Section II also covers sex crimes; theft, burglary, robbery, and arson; enterprise and white-collar crime, and terrorism. The book is illustrated throughout with a variety of Exhibits: photographs and drawings, flowcharts, facsimiles of police documents, and other instructive visuals. Each chapter begins with an engaging vignette, some based on high-profile news articles and others drawn from the author's extensive experience. Interactive features-Case Focus, You Call It, and You Write It-occur at strategic points in every chapter, challenging students to answer questions and apply concepts to actual cases and fictional scenarios. Each chapter ends with a return to the Investigative Triangle, assessing how it applies to the chapter's main topics. Chapters 1-7 (Section I) each include a list of Important Cases (court decisions relevant to the chapter's key concepts). At the end of every chapter (Sections I and II), the Investigate Further feature provides an annotated list of readings, films, and other resources appropriate for class projects, term papers, and special assignments. Each chapter concludes with review questions and a chapter summary. This book is geared to students in the Criminal Investigation course at both two- and four-year institutions, and will appeal to those aspiring to a career in any field related to criminal investigation"--